Mechanistic Insight Into the Interaction Between Helicobacter pylori Urease Subunit α and Its Molecular Chaperone Hsp60 - Zhao, Huilin; Wu, Yulong; Xu, Zheng; Ma, Ran; Ding, Yunfei; Bai, Xuelian; Rong, Qianyu; Zhang, Ying; Li, Boqing; Ji, Xiaofei (Frontiers in Microbiology, 2019)
Helicobacter pylori is the etiologic agent in a variety of gastroduodenal diseases. As its key pathogenic factors, both urease and Hsp60 play important roles in the pathogenesis of H. pylori. Previous studies have suggested that there is close relationship between urease and Hsp60, which implied that Hsp60 may act as a chaperone in urease stabilization and assembly. However, how these two proteins interact remains unclear. In this study, the impact of Hsp60 on urease activity of H. pylori lysate was first detected to confirm the interaction between urease and Hsp60. Pull-down assays further indicated that Hsp60 could bind to UreA subunit but not UreB. Then, the 3D structure of Hsp60 was modeled using I-TASSER to simulate the binding complex with UreA by molecular docking. The results showed that UreA is a perfect fit for the cavity of Hsp60. Analysis of the resulting model demonstrated that at least seven residues of UreA, located on two interfaces, participate in the interaction. Site-directed mutagenesis of these potential residues showed reduced affinity with Hsp60 than the wild type UreA through surface plasmon resonance (SPR) experiments, and D68 appears to have an important role in the affinity. Further analysis also showed that mutation of E25 and K26 caused a more rapid association and dissociation than with wild UreA, implying that they have roles in stabilizing the interaction complex. These affinity comparisons suggested that the interfaces predicted by molecular docking are credible. Our study indicated a direct interaction between Hsp60 and urease and revealed the binding interfaces and key residues involved in the interaction. These results provide further evidence for the chaperone activity of Hsp60 toward urease and lay a foundation to better understand the maturation mechanism of urease in H. pylori.